Determination of the sensitivity of Rhizobium leguminosarum bv.viciae bacteria to the anti-beta-lactam group - Mohammed AL-Taee; Mohammed Alhes (College of Education for Pure Sciences, 2008)
ABSTRACT Rhizobium leguminosarum bv.viciae was isolated and identified from root nodules of Vicia faba L. plant. Its susceptibility to 14 types of -lactam antibiotics was tested by disk diffusion method. The isolate was resistant to the following antibiotics; Amoxicillin, Carbencillin, Cephalexin, Cephradine, Cefuroxime, Cefotaxime, Ceftazidime, Cefixime, Ceftizoxime, Cefepime, and Aztreonam, while it was sensitive to only three antibiotics including; Imipenem, Cefoperazone and Ceftriaxone. The occurrence of multiple drug resistance in a soil bacterium, that is not a pathogen, suggests that chemotherapeutic use of antibiotics is not required for the development of multiple drug resistance. This may considers as a defense line to protect plant roots from pathogenic soil microorganisms.